Perhitungan Daya Output PLTMH di Jalan Bintara Sungai Duren Jambi - Kriswanto Kriswanto; S Umar Djufri (Universitas Batanghari Jambi, 2019)
In Indonesia, not all of them get full electricity, in many regions there are not enough sources of electrical energy, but in Indonesia there are quite a lot of child air currents such as halal rivers because the benefits are as a source of electrical energy, PLTMH is very good to be used in hilly areas with manufacturing costs that are not quite expensive and not so difficult in its workmanship. This PLTMH uses a 2inch pipe size and a waterfall fall that is ideally used 0.2 m and turbine diameter 0.4 radius 0.2 specifier 18 Volt 15 Ampere generator uses 32 ampere / hour battery for storage of power generated by PLTMH and the inverter converts the dc current to ac power generated by PLMH. With the turbine rotation that is obtained by PLTMH 80 Rpm and produces 10.705 Watt turbine output power with generator output power and 7.996 Watt PLTMH output power